INKONSISTENSI KAWASAN HUTAN MENGGUNAKAN SISTEM INFORMASI GEOGRAFI KASUS: KESATUAN PENGELOLAAN HUTAN PRODUKSI (KPHP) MODEL KABUPATEN KAPUAS HULU PROVINSI KALIMANTAN BARAT - , Dwi Kusharyono ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Functions of forests area is an important aspect as the basis for the implementation of sustainable forest management. Inconsistency establishment of forest function may lead to the uses of forest area that are not procedural. Therefore, this study was conducted in order to see the level of inconsistency in the determination of forest spatial pattern maps that is designed by Ministry of Forestry and Spatial Plan Proposed map of Kapuas Hulu Regency 2011-2031. This research use spatial analysis method to every function of forest area in three forest function maps. Determination of the direction of forest area functions is based on Decree of Ministry of Agriculture No. 837/Kpts/Um/11/1980, 683/Kpts/Um/8/1981, Presidential Decree No. 32 year 1990, and Government Regulation No. 44 year 2004. Inconsistency analysis performed using the overlay maps of each area function against the direction of area function. As the result, inconsistency at the study area indicates the hisghest level of inconsistency is forest area in RTRW with 67.13 % while the designation of forest area by the minister at 48.62 %. RTRW also has a great level of inconsistency against the designation for 46.08 %. Inconsistencies occur because of differences in resource of maps, zoning techniques and the use of mapping technologies such as Geographic Information System (GIS). Determination of the function areas that do not pay attention to the physical condition of the area resulting in a massive diversion to land use of forest area such as the existence of a farming area of 8602.41 ha in RTRWK that should be protected forest areas and an area of 688.05 ha area in the designation of the Minister which whole of its is in the fortest area. Inconsistency of forest functions will still be cause conflicts in the management area if it does not have a reference map that has been integrated with other maps such as maps of administrative and other thematic maps and the weak control of the utilization of space. Forest management at the sites is possible to be better, if it has noticed the economic, ecological and socio-cultural aspect as it has been formulated in the second scenario in this study